Synovial Tissue Biopsy Research - Veale, Douglas J. (Frontiers in Medicine, 2019)
Synovial tissue is a key structure in diarthrodial joints and is the primary target of inflammation in autoimmune arthritis. The study of synovial tissue has developed significantly in the last two decades as arthroscopic and ultrasonographic techniques have allowed visualization and access to synovial biopsy. Further progress in synovial tissue processing and analysis has improved studies of disease pathogenesis, biomarker discovery and molecular therapeutic targeting with increasingly specialised analytical and technological approaches. In September 2018 the first course on Synovial Tissue Biopsies was convened in Brussels, in this Mini Review these approaches will be described and I will summarize how synovial tissue research advanced.